Algorithmic Neutrality or Digital Inequality? AI and the Lessons from ISDS - Yağmur Sönmez, Esma (Revista Ítalo-Española de Derecho Procesal, 2026)
The article argues that AI-driven judicial reform initiatives within civil justice systems repeat an established pattern in which critique is absorbed into procedure. Using Investor–State Dispute Settlement (ISDS) as a cautionary mirror, it shows how managerial legality performs neutrality while reproducing inequality. It then outlines a human-centred alternative grounded in participation, accountability, and contestability, calling for a shift from design-led legitimacy to democratic oversight